Participative Urban Air Quality Monitoring Using Open Source Devices - Maurizio Vrenna; Matthieu Crétier; Simon Nelson Landén (Agathón)
Air pollution negatively affects the life quality of billions of people living in urban areas. Current monitoring systems provide accurate data but this is distributed on large-scale grids. It is therefore difficult for citizens and institutions to be fully aware of the air quality in their area. The article presents an interdisciplinary research group’s experimentation, aimed at creating a compact, economic, and easily reproducible device capable of measuring pollutants and reporting them in real-time on a detailed, free-access map. The openness of the code and the versatility of the product are the keys to its replicability and for tackling air pollution with a participatory approach.